2002
DOI: 10.1074/jbc.m208596200
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Ser for Arg-443 in the Regulatory Domain of Human Housekeeping (GLUD1) Glutamate Dehydrogenase Virtually Abolishes Basal Activity and Markedly Alters the Activation of the Enzyme by ADP and l-Leucine

Abstract: Human glutamate dehydrogenase (GDH) exists in GLUD1 (housekeeping) and in GLUD2-specified (brainspecific) isoforms, which differ markedly in their basal activity and allosteric regulation. To determine the structural basis of these functional differences, we mutagenized the GLUD1 GDH at four residues that differ from those of the GLUD2 isoenzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 36 publications
8
75
0
Order By: Relevance
“…Structural analyses of the R443S mutant have suggested that introduction of Ser 443 disrupts side chain bonds in the antenna between Arg 443 of one subunit and Ser 409 of the adjacent subunit, leading to a closed conformation (15). This possibility is supported by additional studies 3 showing that substituting Arg for Ser 409 , which also disrupts the above side chain bonds, diminishes basal activity.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Structural analyses of the R443S mutant have suggested that introduction of Ser 443 disrupts side chain bonds in the antenna between Arg 443 of one subunit and Ser 409 of the adjacent subunit, leading to a closed conformation (15). This possibility is supported by additional studies 3 showing that substituting Arg for Ser 409 , which also disrupts the above side chain bonds, diminishes basal activity.…”
Section: Discussionsupporting
confidence: 63%
“…Initially, we studied the S409(R/D) hGDH1 mutants, which, similar to the R443S hGDH1 mutant, show low basal activity. 3 Introduction of Arg at residue 409 is thought to disrupt side chain bonds in the antenna region between Arg 443 of one subunit and Ser 409 of the adjacent subunit (15). Functional analyses of the expressed enzyme, purified to homogeneity, revealed that the S409R-hGDH1 mutant was indeed much more sensitive to estrogens than the wild-type hGDH1 (Fig.…”
Section: Study Of Hgdh1 and Hgdh2 Mutants Reveals That Sensitivity Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, to achieve full-range regulation by these activators, hGDH2 needs to set its basal activity at low levels (about 4-8% of full capacity), a property largely conferred by the evolutionary Arg443Ser change. 29 Hence, the detected Ser445Ala change has altered a property that is crucial for the tight regulation of hGDH2. 13 Substitution of Ala for Ser445 is predicted by secondary structure prediction programs 30 to stabilize the small á-helix of the antenna.…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocally interchanging amino acids that are different between hGDH isozymes within the regulatory domain may reveal the residues important for preference in hGDH isozymes. Recent studies of structure-function relationships using site-directed mutagenesis of hGDH1 at single sites differing from hGDH2 showed that the R443S and the G456A change reproduced some but not all of the properties of hGDH2 (3)(4)(5)17). In addition, several other residues differing between hGDH isozymes also have been examined by many investigators (4,17).…”
mentioning
confidence: 99%